Is the urinary kidney injury molecule an optimum biomarker for early detection of obstructive nephropathy? An experimental study - Ahmed S El-Hefnawy; Mona A El-Hussiny; Ahmed M. A Ibrahim; Khadiga M Ali; Mohammed A Atwa; Nashwa Barakat; Mohamed Alhefnawy; Ahmed A Shokeir (Current Urology)
Abstract. Objectives. To evaluate the urinary kidney injury molecule-1 (KIM-1) as a predictor for early detection of acute kidney injury in cases with obstructive nephropathy in an animal model and to correlate urinary KIM-1 with the progress of obstructive nephropathy on a histopathological basis. Materials and methods. Three models of obstruction were induced in 90 male rats: unilateral partial ureteral obstruction with a normal contra-lateral kidney, with nephrectomy of a contralateral kidney (solitary kidney), and bilateral partial ureteral obstruction. Each group was further divided into 2 subgroups; the sham-group (10 rats) and the disease group (20 rats). Serum creatinine, blood urea nitrogen, and urinary KIM-1 were collected on days 0, 7, and 14. Rats were sacrificed on the 7th and 14th day for histopathological examination of the obstructed kidney. Results. By the end of first week, there was a significant rise of all biomarker levels in all groups when compared with basal levels. Similarly, biomarker levels at the 14th day were significantly higher than those obtained at the 7th day. The urinary KIM-1 level was not detected in the baseline condition. Expression of urinary KIM-1 showed a significant rise in all models ranging from 22 to 85 fold at the 7th day and even higher levels at the 14th day. Histopathological examination confirmed the presence of different forms of tubular injury. Conclusions. Urinary KIM-1 is significantly elevated in obstructive uropathy. Such an elevation might be advantageous in the early diagnosis and subsequent early intervention of cases with partial ureteral obstruction.